Pengaruh Ekstrak Kulit Manggis dalam Mencegah Peningkatan Kadar Blood Urea Nitrogen pada Tikus Putih (Rattus norvegicus) Galur Wistar yang Diinduksi Gentamisin - Winiasih, Putri Ayu; Hardjanti, Endang Sri; Hikmayani, Nur Hafidha (Nexus Biomedika, 2014)
Background: Gentamicin, which is often used for infection treatment against aerobic Gram negative bacteria, is known having nephrotoxic effects through the inflammation mechanisms. Mangosteen pericarp has antioxidant activity and antiinflammation properties which attenuates oxidative stress, inflammatory and fibrotic pathways, hence it potentially prevents renal damages. Gentamicin-induced renal damages can be measured from elevation of blood urea nitrogen (BUN) levels. The aim of this study was to evaluate the effect of mangosteen pericarp extract on BUN levels in Wistar rats induced by gentamicin. Methods: This was an experimental study with pre- and posttest controlled group design. Thirty white male Wistar rats aged 8-12 weeks and weighed 135-170 grams were randomly divided into three groups. Normal control group (P1) was administered Â orally with Natrium Carboxymethylcellulose (Na CMC) 0.5%. Negative control group (P2) got intraperitoneal (i.p.) injection of gentamicin at total dose of 100 mg/kgBW. Treatment group (P3) was induced by gentamicin and 125 mg/kgBW mangosteen pericarp extract. The extract was administered orally thirty minutes after gentamicin injection for ten consecutive days. Blood samples were collected from retroorbital veins and BUN levels were measured at day 0 and day 11. Data were analyzed statistically by one-way ANOVA followed by Tukeyâs multiple comparison tests (Î±=0.05). Results: One-way ANOVA test showed no significant difference in pretest BUN levels among three groups (p=0.902). At day 11, BUN level in P2 group was significantly higher than those in P1 and P3 groups. Tukeyâs multiple comparison test further showed significant difference between P1-P2 and P2-P3 (p<0.001). No significant difference of BUN level was found between P1-P3 (p=0.386). Conclusions: Mangosteen pericarp extract could significantly prevent the elevation of BUN levels in Wistar rats induced by gentamicin. Keywords: mangosteen pericarp extract, gentamicin, BUNÂ